Efficient Procedure for N-Glycan Analyses and Detection of Endo H-Like Activity in Human Tumor Specimens - Lattová, Erika; Bryant, Joseph; Skřičková, Jana; Zdráhal, Zbyněk; Popovič, Mikuláš (Journal of proteome research, 2016)
Although the importance of glycosylation has been thoroughly recognized in association with a number of biological processes, efficient assessments of glycans have been hampered by both the limited size of specimens and lengthy sample preparations, particularly in clinical settings. Here we report a simple preparative method for N-glycan analyses. It involves only short one-step chloroform-methanol extraction in presence or absence of water prior to PNGase F deglycosylation. The procedure was successfully applied to the investigation of N-glycans obtained from small numbers of in vitro cultured cancer cells (≤1 × 10(5)) and to tumor tissues, including patient biopsies of small size. MALDI-MS analysis confirmed the efficient release of all N-glycan types including complex forms with poly-N-acetyllactosamine chains. In addition, nonaqueous extraction of specimens from several established cancer cell lines, as well as patient tumor tissues, yielded high-mannose glycans with one GlcNAc moiety (Man3-9GlcNAc), strongly suggesting preservation of enzymatic activity analogous to Endo H enzyme. In summary, the method is both a step toward the practical use of glycan profiling and a way to detect Endo H-like activity in cancer specimens.
Keywords: velikost vzorku; glykopeptidasa; mannosa; glycosylation; Sample Size; mannosyl-glykoprotein endo-beta-N-acetylglukosaminidasa; Neoplasms; Tumor Cells, Cultured; Polysaccharides; Glycosylation; tumor tissue; Biopsy; EndoH; glycans; Mannosyl-Glycoprotein Endo-beta-N-Acetylglucosaminidase; nádorové buňky kultivované; mass spectrometry; spektrometrie hmotnostní - ionizace laserem za účasti matrice; cancer cells; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; glykosylace; lidé; nádory; Humans; Peptide-N4-(N-acetyl-beta-glucosaminyl) Asparagine Amidase; Mannose; polysacharidy